Coping strategies and changes in type D personality were associated with depressive tendency at 9 months after percutaneous coronary intervention. - Daisuke Yamaguchi; Yoshihiro Asano; Koichiro Kuwahara; Atsushi Izawa (PLoS ONE)
Type D personality, characterized by negative affectivity and social inhibition, has been associated with both the psychophysiology of coronary artery disease (CAD) and depressive disorders. However, few reports have described the impact of coping strategies in these patients. This study aimed to analyze the characteristics of type D personality and the coping strategies adopted by patients with CAD and to explore the factors associated with depressive tendencies during follow-up. Among 84 patients with CAD (median age 66.5 years, nine women) who underwent percutaneous coronary intervention (PCI), we examined pre-discharge characteristics for personality and coping strategies. We prospectively evaluated associations with the persistence or improvement of depressive tendencies at 9 months. Our findings revealed that persistence of depressive tendencies at 9 months was inversely associated with the adoption of the "planning" coping strategy (odds ratio [OR]: 0.80). We observed worsening depressive tendencies in patients with type D personality who transitioned from non-type D during follow-up. Conversely, improvement in depressive tendencies was associated with the adoption of "planning" (OR: 1.47), "evasive thinking" (OR: 1.47), and "positive interpretation" (OR: 1.43) coping strategies, and inversely associated with the adoption of the "abandonment or resignation" strategy (OR: 0.71). The persistence or improvement of depressive tendencies at 9 months post-PCI was associated with the adoption of specific coping strategies. Changes in type D personality during follow-up were associated with the status of depressive tendency. Personality-oriented treatment incorporating specific coping strategies may provide new strategies to prevent depression and improve care for patients with CAD.